Divergent changes in particulate and mineral-associated organic carbon upon permafrost thaw - Liu, Futing; Qin, Shuqi; Fang, Kai; Chen, Leiyi; Peng, Yunfeng; Smith, Pete; Yang, Yuanhe (Nature communications, 2022)
Permafrost thaw can stimulate microbial decomposition and induce soil carbon (C) loss, potentially triggering a positive C-climate feedback. However, earlier observations have concentrated on bulk soil C dynamics upon permafrost thaw, with limited evidence involving soil C fractions. Here, we explore how the functionally distinct fractions, including particulate and mineral-associated organic C (POC and MAOC) as well as iron-bound organic C (OC-Fe), respond to permafrost thaw using systematic measurements derived from one permafrost thaw sequence and five additional thermokarst-impacted sites on the Tibetan Plateau. We find that topsoil POC content substantially decreases, while MAOC content remains stable and OC-Fe accumulates due to the enriched Fe oxides after permafrost thaw. Moreover, the proportion of MAOC and OC-Fe increases along the thaw sequence and at most of the thermokarst-impacted sites. The relatively enriched stable soil C fractions would alleviate microbial decomposition and weaken its feedback to climate warming over long-term thermokarst development. Based on observations from thermokarst-impacted sites on the Tibetan Plateau, the authors find substantial particulate organic carbon loss but stable mineral-associated organic carbon and enriched iron-bound organic carbon upon permafrost thaw.